2019
DOI: 10.1088/1757-899x/528/1/012066
|View full text |Cite
|
Sign up to set email alerts
|

Mapping of noise levels made by drilling machines on project x using contour zone method

Abstract: Project x is an apartment development activities in Tangerang which in the process of construction resulted in the occurrence of noise. Noise is one of the incidents that can be lead to health problems for the surrounding community. Therefore, this research aims to know the spread of noise, the amount of noise reduction that can be reduced by using a hearing protective device and workers’ perceptions of noise against hearing loss. The method used is the contour zone. Data used is the result of noise measuremen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…Earmuffs can reduce noise pressure around 25-40 dB, while earplugs can reduce noise pressure around 8-30 dB. 24 It depends on whether or not the respondent loosens the earplugs. 25 Similar study results from Yovi and Suryaningsih 21 showed that the chainsaw operators and harvesting workers have a significantly different perception on the chainsaw sounds in each chainsaw mode (idle, half-gas, racing) and when using or not using ear protectors.…”
Section: Resultsmentioning
confidence: 99%
“…Earmuffs can reduce noise pressure around 25-40 dB, while earplugs can reduce noise pressure around 8-30 dB. 24 It depends on whether or not the respondent loosens the earplugs. 25 Similar study results from Yovi and Suryaningsih 21 showed that the chainsaw operators and harvesting workers have a significantly different perception on the chainsaw sounds in each chainsaw mode (idle, half-gas, racing) and when using or not using ear protectors.…”
Section: Resultsmentioning
confidence: 99%
“…The analysis results obtained from data retrieval are processed into a descriptive analysis. By using software that supports data, analysis obtained is valid, accurate and actual [11][12][13].…”
Section: Methodsmentioning
confidence: 99%
“…Earmuffs can reduce noise pressure around 25-40 dB, while earplugs can reduce noise pressure around 8-30 dB. 25 It depends on whether or not the respondent loosens the earplugs. 26 Similar study results from Yovi and Suryaningsih 27 showed that the chainsaw operators and non-chainsaw operators have a significantly different perception on the chainsaw sounds in each chainsaw mode (idle, half-gas, racing) and when using or not using ear protectors.…”
Section: Respondents' Perception Toward Noisementioning
confidence: 99%
“…28 These ear protectors are usually used for protection up to 110 dB. 25 The disadvantage is that they can be uncomfortable for prolonged use in hot environments and interferes with the use of other protective equipment, such as goggles. 28 Meanwhile earplugs, being small and lightweight, tend to be more comfortable and easy to combine with other protective equipment such as hats and goggles, but because it needs to be inserted to the ear canal, it is more difficult to monitor the use of earplugs compared to earmuff and requires special fitting instructions.…”
Section: Respondents' Perception Toward Noisementioning
confidence: 99%